Table of Content - - (Journal of Educational and Psychological Sciences, 2025)
Table of Content: 1. The Level of Cybersecurity Awareness among Graduate Female Students at King Saud University Ms. Ahad Abdulkader Altayeb ,Ms. Najla Turki Alwahbi ,Ms. Noura Ahmed Almoqren 2. The reality of professional development for public school teachers in Lebanon and its obstacles from the perspective of a sample of principals: Teacher training in the Beirut Governorate as a model Mr. Ali Habib Mhanna 3. Future scenarios for applying artificial intelligence techniques at the Training Department at A Saudi government university Ms. Dalia Abdulaziz Al-Harbi ,Ms. Maryam Abdullah Al-Luhidan ,Ms. Salwa Abdo Mohammed ,Ms. Jamilah Faisal Al-Kathiri ,Prof. Fatima Abdulaziz Al-Tuwaijri 4. The Effectiveness of Supervisory Methods on Teachers’ Performance in Schools Affiliated with Al-Ulaya Education Office in Riyadh Dr. Abdulaziz Nasser Al-Fadhil 5. The Level of School Health Environment in the General Directorate of Education in Taif Governorate from the Perspective of Health Supervisors and Its Relationship with Some Variables Dr. Sulaiman Hamoud Al-Salmi,Mr. Mutaib Hashim Al-Hashaibri 6. Psychometric Properties of the Assertive Behavior Scale for a Sample of Adolescents in Makkah Region Mr. Muhammad Yahya Al-Hazzazi,Co-Prof. Saleh Yahya Al-Ghamdi 7. Social networks and their relevance to children’s mental health from the perspective of mothers Ms. Ghaida Saud Al-Rehden